Oral Health Literacy and Behaviour of Health Sciences University Students - Ying, Ng Yee; Ming, Lye Shen; Said, Shahida Mohd-; Yusof, Noriah; Mohd-Dom, Tuti N Mohd-Dom N (Journal of Dentistry Indonesia, 2015)
Objective: This study aimed to determine the level of oral health literacy and behavior among health sciences university students. Methods: The method used descriptive cross-sectional survey involving 609 students from Faculty of Medicine, Dentistry, Pharmacy and Allied Health Sciences in the Universiti Kebangsaan Malaysia. Oral health literacy level and behaviour was assessed with a validated and pretested self-administered questionnaire using the Newest Vital Sign (NVS) tool and modified Oral Health Adult Literacy Questionnaire (OHL-AQ). Results: A total of 509 participants involved in the study (83.6%). The overall mean oral health literacy score was 10.27 (95% CI 7.92, 12.62), which found dental students showing statistically significant higher scores (mean=11.36, 95% CI 9.70, 13.02) compared to medical (mean=10.72, 95% CI 8.67, 12.77), allied health sciences (mean=9.89, 95% CI 7.34, 12.44) and pharmacy (mean=9.55, 95% CI 7.23, 11.87). Almost all respondents are non-smokers (99.8%) and non-drinkers (97.2%). Only 19.1% pay regular dental visits every 6-12months while 51.1% visit dentist only when they have dental pain. There appears to be a positive relationship between oral health literacy and oral health behavior. Conclusion: Health science university students should be provided substantial dental health education in their curriculum as they could be potential strategic partners in oral health.